The dinoflagellate Alexandrium minutum affects development of the oyster Crassostrea gigas, through parental or direct exposure. (March 2019) - Castrec, Justine; Hégaret, Hélène; Alunno-Bruscia, Marianne; Picard, Maïlys; Soudant, Philippe; Petton, Bruno; Boulais, Myrina; Suquet, Marc; Quéau, Isabelle; Ratiskol, Dominique; Foulon, Valentin; Le Goïc, Nelly; et al.
Abstract: Harmful algal blooms are a threat to aquatic organisms and coastal ecosystems. Among harmful species, the widespread distributed genus Alexandrium is of global importance. This genus is well-known for the synthesis of paralytic shellfish toxins which are toxic for humans through the consumption of contaminated shellfish. While the effects of Alexandrium species upon the physiology of bivalves are now well documented, consequences on reproduction remain poorly studied. In France, Alexandrium minutum blooms have been recurrent for the last decades, generally appearing during the reproduction season of most bivalves including the oyster Crassostrea gigas . These blooms could not only affect gametogenesis but also spawning, larval development or juvenile recruitment. This study assesses the effect of toxic A. minutum blooms on C. gigas reproduction. Adult oysters were experimentally exposed to A. minutum, at environmentally realistic concentrations (10 2 to 10 3  cells mL −1 ) for two months during their gametogenesis and a control group, not exposed to A. minutum was fed with a non-toxic dinoflagellate. To determine both consequences to next generation and direct effects of A. minutum exposure on larvae, the embryo-larval development of subsequent offspring was conducted with and without A. minutum exposure at 10 2  cells mL −1 . Effects at each stage of the reproduction were investigated on ecophysiological parameters, cellular responses, and offspring development. Broodstock exposed to A. minutum produced spermatozoa with decreased motility and larvae of smaller size which showed higher mortalities during settlement. Embryo-larval exposure to A. minutum significantly reduced growth and settlement of larvae compared to non-exposed offspring. This detrimental consequence on larval growth was stronger in larvae derived from control parents compared to offspring from exposed parents. This study provides evidence that A. minutum blooms, whether they occur during gametogenesis, spawning or larval development, can either affect gamete quality and/or larval development of C. gigas, thus potentially impacting oyster recruitment. Graphical abstract: Image 1 Highlights: Two-month exposure of adult oysters to Alexandrium minutum decreased sperm motility. Oocytes and spermatozoa of exposed oysters contained paralytic shellfish toxins. Larvae derived from these gametes showed reduced growth and survival. Exposure of oyster larvae to A. minutum altered larval growth and settlement. Adult exposure influenced offspring response to A. minutum exposure. Abstract : The toxic dinoflagellate Alexandrium minutum affected larval development of the oyster Crassostrea gigas, directly through exposure of larvae and indirectly through parental exposure during gametogenesis.